À sombra das chuteiras virtuais: futebol e lazer nas quatro linhas do jogo eletrônico - Mariana Alves Rodrigues (2011)
This study aimed to investigate the relationships that emerge from soccer in the context of virtual game. Specifically, we sought to identify, with players from the Federação Luziense de Futebol Digital FLFD, experiences surrounding this game as well as the relations between these individuals and soccer, virtual and non-virtual. For this, the literature guided this work and, for nine months, an immersion in thevirtual community of that federation was done. The face contact was made through three visits to the federation's building in Santa Luzia-MG, beyond monitoring the Copa Sudeste de Futebol Digital and the Campeonato Mineiro de Futebol Virtual, events occurred in 2010 that were attended by the members of FLFD. The field research was carried out by tracking sporadic games, training, experience exchanges in the virtual community, contact with members of the federation, as wellas events organized by them and participation in other events. Anyway, the most diverse experiences shared among the possible actors in the network consisted as production sources of data for the research. The field record book was the main instrument for recording data, in addition to textual material produced by the virtual community. It was possible to establish that FLFD players maintain a relationship with non-virtual soccer, which is expressed through language, interest in the currentchampionships, by rivalry and belonging to a club. As for the virtual game, it was noticed that there is a sense of belonging and rivalry, apart from manifestations of hope, passion and superstition. Finally, it was also possible to verify that leisure is imbued with the experiences in the context of virtual soccer on FLFD.